Analysis of Income and Profits on Eid Al-Fitr Package Savings in Tempuran Karawang District - Tasya Tania Putri; Dedi Mulyadi; Santi Pertiwi Hari Sandi (International Journal of Economics and Management Research, 2025)
Indonesian people often face financial pressures, especially during Eid preparations, and need financial solutions. Special savings programs such as Eid al-Fitr emerged as a way to help people plan their finances. This research was conducted on Eid package savings owners in Cikuntul Village which has the largest number of participants, namely 168 customers. This study aims to analyze income and profits from Eid al-Fitr package savings in Tempuran District, Karawang Regency. This program offers a variety of package options, such as chicken, beef, basic necessities, cakes, and money, with a payment period of 11 months. The research method used was qualitative descriptive through observation, interviews, and documentation from the period of May 2023 to March 2024. The results of the study explain that in the implementation of this Eid package savings activity, it provides benefits for the participants who follow it. This activity not only helps participants in preparing for their needs ahead of Eid, but also encourages participants in managing finances ahead of Eid al-Fitr. In its implementation, the Rp. 3,000 and Rp. 5,000 packages are the most popular package choices by participants. The trust of the people who participate in this activity is very important for the sustainability of the Eid package savings. The profit generated on the Eid package savings managed by Mrs. Eva shows that the Eid package savings managed to provide a profit of Rp. 26,468,700 from all types of packages offered.